The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/aos.12448
|View full text |Cite
|
Sign up to set email alerts
|

Ocular findings in 87 adults with Ghent‐1 verified Marfan syndrome

Abstract: ABSTRACT.Purpose: To study ocular characteristics in 87 patients with verified Marfan syndrome (MFS) based on the Ghent criteria from 1996 (Ghent-1). Methods: The position of the lens was noted by observing the eye in different gaze directions in maximal mydriasis during slit lamp examination. Ectopia lentis (EL) was classified as subluxated (dislocation slightly backwards) or luxated (vertical or horizontal displacement). Corneal curvature, axial length (AL), corneal diameter, central corneal thickness, anter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
5
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 40 publications
(115 reference statements)
6
65
5
4
Order By: Relevance
“…Previous studies on patients with MFS showed an average AL of 24.0–25.0 mm. 3,5,7,11,12 This AL is relatively longer compared to population studies on healthy patients, which suggest a normal AL of approximately 23.5 mm. 13,14 Our study confirms these previous reports, with an average AL of 25.25 mm in adults and 24.24 mm in children.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Previous studies on patients with MFS showed an average AL of 24.0–25.0 mm. 3,5,7,11,12 This AL is relatively longer compared to population studies on healthy patients, which suggest a normal AL of approximately 23.5 mm. 13,14 Our study confirms these previous reports, with an average AL of 25.25 mm in adults and 24.24 mm in children.…”
Section: Discussionmentioning
confidence: 70%
“…Although it is no longer considered a criterion for MFS, it should be suspected in patients with longer AL and a flat cornea. 7 According to previous reports, myopia >3 D is a nonspecific criterion for MFS, with a prevalence of about 30–40% in patients with MFS. 3,5,7 However, the refractive error of all MFS subjects <5 years of age (Table 3), when it was known, showed high to very severe myopia (range −3.75 to −26 D).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Compared with patients with MFS, myopia in patients with LDS appears to be less frequent and less severe 4. Drolsum and colleagues12 reported a mean spherical equivalent of −4.08 dpt in patients with MFS, with myopia being higher in eyes with EL (spherical equivalent: −5.85±8.69 dpt). In that study, the mean refractive error of eyes without EL (spherical equivalent, −2.20±3.52 dpt) was comparable to that of LDS eyes in our study.…”
Section: Discussionmentioning
confidence: 97%
“…While in the beginning, stent-grafting was advocated in patients with MFS, it soon became evident that the endoleak and secondary intervention rates were much higher than in patients without MFS 56,57. The reason is presumably the fixation of the vascular prostheses in the aortic vessel.…”
Section: Team Membersmentioning
confidence: 99%